Penerapan model pembelajaran problem based learning untuk meningkatkan hasil belajar IPAS siswa kelas 3 di Sekolah Dasar - Imroatus Sholikah; Yuni Ratnasari; Oktri Suhartati; Taris Fadhlil Wafi (Jurnal Pendidikan Dasar, 2025)
This classroom action research was conducted to analyze the implementation of the Problem-Based Learning (PBL) model in improving the learning outcomes of third-grade students at SD 3 Peganjaran, Kudus. The study followed four key stages: planning, implementation, observation, and reflection, involving 12 students. Data collection techniques included teacher interviews, observations of student and teacher learning activities, and test assessments to measure student achievement based on a minimum competency indicator of ≥ 70. The findings revealed a significant improvement in student mastery, increasing from 50% in the pre-cycle to 66.7% in cycle 1, and reaching 100% in cycle 2. Since students’ learning outcomes met the classical mastery threshold of 75%, the Problem-Based Learning method was proven to be effective in enhancing student achievement, fostering critical thinking, and promoting active learning. Moreover, the study demonstrated that PBL encourages students to engage more deeply with learning materials, collaborate with peers, and develop problem-solving skills. Thus, the PBL model not only improves learning outcomes but also actively cultivates critical thinking skills, which are essential for shaping students' analytical and creative reasoning abilities.